Existential Philosophy and Disability : Perspectives - Fox-Muraton, Mélissa (New Research in the History of Western Philosophy, 2025)
This volume proposes a novel approach to engaging philosophically with disability studies. Taking as a starting point the fact that disability is an integral part of human existence, the chapters in this volume provide insight into situated, lived experiences of disability in articulation with prominent existential philosophers. Historical and theoretical perspectives bring the dominant models of understanding disability today (medical or biomedical and social) into dialogue with existential philosophical perspectives, and thematic contributions provide insight into specific disabled experiences which have historically been underrepresented in philosophy, including mental illness, addiction, severe cognitive/intellectual disability, ADHD, autism, and neurodivergent communication.